2017
DOI: 10.1002/sim.7219
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the precision of mediation analyses of randomised experiments through covariate adjustment

Abstract: Analyses of randomised experiments frequently include attempts to decompose the intention-to-treat effect into a direct and indirect effect, mediated by given intermediaries, with the aim to shed light onto the treatment mechanism. Methods from causal mediation analysis have facilitated this by allowing for arbitrary models for the outcome and the mediator. They thereby generalise the traditional approach to direct and indirect effects, which is essentially limited to linear models. The default maximum likelih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…A change score approach was again found to be suffering from bias when baseline measures predicted subsequent change. Finally in line with the study by Vandenberghe et al, 26 we found that for continuous mediators and outcomes results were robust against misspecification of the mediator model.…”
Section: Discussionsupporting
confidence: 92%
“…A change score approach was again found to be suffering from bias when baseline measures predicted subsequent change. Finally in line with the study by Vandenberghe et al, 26 we found that for continuous mediators and outcomes results were robust against misspecification of the mediator model.…”
Section: Discussionsupporting
confidence: 92%
“…To examine the hypothesized change mechanisms of SC-PIES (RQs 3 and 4), we sequentially explored the mediation effect of ITI on the relationship between study conditions and intervention fidelity, followed by a secondary model where teachers' fidelity was hypothesized to mediate the relationships between their ITI and class-wide AET. To control for baseline status, the mediation models were fitted with change scores that were calculated by subtracting pretest values from the posttest (Vandenberghe et al, 2017). The nonparametric bootstrapping mediation analysis was used rather than the causal steps approach (Baron & Kenny, 1986) because of its superior capacities to handle small samples, estimate robust standard errors, and detect mediation effects without significant total effects (Hayes, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hsu et al outlined a conceptual framework for a counterfactual mediation model for time‐varying exposures and time‐varying surrogates 36 . Vandenberghe et al described a counterfactual‐based model for surrogate evaluation with a binary mediator and a continuous or binary true endpoint 37 . They proposed several estimators using propensity score‐based models and generalized linear models.…”
Section: Discussionmentioning
confidence: 99%